PENGEMBANGAN MEDIA PEMBELAJARAN E-LEARNING BERBASIS MOODLE PADA MATERI PECAHAN SENILAI KELAS IV SEKOLAH DASAR - Meisya Widyasusanti; Iva Sarifah; Herlina Usman (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This research and development produced a market-tested media and is suitable to be used by educators. This education media help students in their learning process whilst still having fun, especially in the topic of fractions. This research and development was built using the ASSURE model and adopted the evaluation process by Dick and Carey. The subjects of this RnD are the students from SDN Ragunan 01 Jakarta Selatan's 4th grade class, with a total of 18 students. Data collection was done through interviews and questionnaires and with Miles and Huberman data anlysis. Results of the research show that e-learning on Moodle is a learning media worth using, in this case for the purpose of teaching fractions to 4th graders. The results show an impressive expert review average score of 87.2% by the subjects in their understanding of the lesson. This media received positive response from the 3 selected students during the one to one tryout stage and a 96.42% mark by the subjects during the field trial stage. It is evident that this moodle-based e-learning media is properly made, well tested, and suitable for use in the education field - specifically for the purpose of teaching fractions to 4th graders.